Cross-disorder analysis of bipolar risk genes: Further evidence of dGKH as a risk gene for bipolar disorder, but also unipolar depression and adult ADHD - Weber, Heike; Kittel-Schneider, Sarah; Gessner, Alexandra; Domschke, Katharina; Neuner, Maria; Jacob, Christian P.; Buttenschon, Henriette N.; Boreatti-Hümmer, Andrea; Volkert, Julia; Herterich, Sabine; Baune, Bernhard T.; Gross-Lesch, Silke; et al. (Neuropsychopharmacology, 2011)
Recently, several genome-wide association studies (GWAS) on bipolar disorder (BPD) suggested novel risk genes. However, only few of them were followed up and further, the specificity of these genes is even more elusive. To address these issues, we genotyped SNPs in ANK3, CACNA1C, CMTM8, DGKH, EGFR, and NPAS3, which were significantly associated with BPD in previous GWAS, in a sample of 380 BPD patients. Replicated SNPs were then followed up in patients suffering from unipolar depression (UPD; n387) or adult attention-deficit/ hyperactivity disorder (aADHD; n535). While we could not confirm an association of ANK3, CACNA1C, and EGFR with BPD, 10 SNPs in DGKH, CMTM8, and NPAS3 were nominally associated with disease, with two DGKH markers surviving correction for multiple testing. When these were followed up in UPD and aADHD, seven DGKH SNPs were also associated with UPD, while one SNP each in NPAS3 and CMTM8 and four in DGKH were linked to aADHD. Furthermore, a DGKH haplotype consisting of rs994856/rs9525580/rs9525584 GAT was associated with all disorders tested, while the complementary AGC haplotype was protective. The corresponding haploblock spans a 27-kb region covering exons coding for amino acids 65-243, and thus might include functional variants yet to be identified. We demonstrate an association of DGKH with BPD, UPD, and aADHD by applying a two-stage design. These disorders share the feature of mood instability, so that this phenotype might be associated with genetic variation in DGKH. © 2011 American College of Neuropsychopharmacology. All rights reserved.
CRIS-Team Scopus Importer:2026-04-08
Keywords: adult ADHD; association; bipolar disorder; CMTM8; depression; NPAS3